2020
DOI: 10.1007/s10508-020-01665-3
|View full text |Cite
|
Sign up to set email alerts
|

Speech Acoustic Features: A Comparison of Gay Men, Heterosexual Men, and Heterosexual Women

Abstract: Potential differences between homosexual and heterosexual men have been studied on a diverse set of social and biological traits. Regarding acoustic features of speech, researchers have hypothesized a feminization of such characteristics in homosexual men, but previous investigations have so far produced mixed results. Moreover, most studies have been conducted with English-speaking populations, which calls for further cross-linguistic examinations. Lastly, no studies investigated so far the potential role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
0
11
1
3
Order By: Relevance
“…Acoustic results showed that the gay group had a lower F0 level (especially at the H-pitch targets) and a narrower F0 range than the heterosexual group. In comparison to previous reports on Western languages, this contradicts Munson et al (2006), Kachel et al (2018) and Suire et al (2020) who found no significant difference in F0 between gay and heterosexual men. Also, the gay group showed a smaller tVSA than the heterosexual group.…”
Section: Discussioncontrasting
confidence: 99%
“…Acoustic results showed that the gay group had a lower F0 level (especially at the H-pitch targets) and a narrower F0 range than the heterosexual group. In comparison to previous reports on Western languages, this contradicts Munson et al (2006), Kachel et al (2018) and Suire et al (2020) who found no significant difference in F0 between gay and heterosexual men. Also, the gay group showed a smaller tVSA than the heterosexual group.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, although our studies were inspired by the finding that actual gender differences in pitch have decreased substantially over time, we focused on how differences in pitch affect perceiver judgments of the speakers’ gender-related attributes. A complementary body of research has examined differences in pitch from the speaker’s perspective and identified both within- and between-gender variations, for example, with respect to sexual orientation (e.g., Kachel et al, 2018; Suire et al, 2020). Studying the convergence between actual and perceived differences in pitch between speakers differing by sex or sexual orientation may inform research on stereotype accuracy with regard to impressions formed on the basis of vocal cues and on social stereotyping more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in the physiological basis of pitch, men generally speak at a lower pitch compared with women. Pitch also shows substantial variability within gender groups, for example in relation to sexual orientation (e.g., Suire et al, 2020), and the difference between men and women has been shown to decrease over the last decades. A study with a representative sample of almost 2,500 men and women aged between 40 and 79 years in Germany found that the mean fundamental speaking voice frequency across different tasks was 168.5 Hz for women and 111.9 Hz for men (Berg et al, 2017).…”
Section: Pitch As a Cue For Masculinity And Femininitymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous stylistic factors can interact when someone is constructing a persona in a conversation, and this is made even more difficult when analyzing their speeches because there are two sets of stylistic phonetic factors (indexical fields) available to the speakers that come from two different cultural ideologies [9]. In contrast, the study by Suire et al [16] found that gay males had values that were more like those of heterosexual women and much greater pitch modulation patterns and less breathy voices than did heterosexual men. Pre-consonantal and syllable-final /s/ will be aspirated less frequently, gay men's speech will have a higher pitch and more clearly articulated vowels than straight men's, and gay men's speech will have a more noticeable pitch contour [7].…”
Section: Introductionmentioning
confidence: 99%